Characterization of the complete mitochondrial genome of the lung fluke, Paragonimus kellicotti. Issue 2 (3rd July 2018) - Wang, Tao; Wang, Yunfang; Xu, Fengqiang; Li, Xia; Qu, Rui; Song, Lin; Tang, Yongping; Lin, Peilin
Abstract: In this study, the complete mitochondrial genome of human lung fluke, Paragonimus kellicotti, was recovered through Illumina sequencing data. This complete mitochondrial genome of P. kellicotti is 13, 927 bp in length and has a base composition of A (16.6%), T (41.8%), C (13.%), and G (28.4%), demonstrating an obvious bias of high AT content (58.4%). The mitochondrial genome contains a typically conserved structure, encoding 12 protein-coding genes (PCGs), 22 transfer RNA genes (tRNA), 2 ribosomal RNA genes (12S rRNA and 16S rRNA), and a control region (D-loop region). All PCGs were located on the H-strand. ND4 gene and ND4L gene were overlapped by 39 bp. The nucleotide sequence of 12 PCGs of P. heterotremus and other 10 parasite species were used for phylogenetic analysis. The result indicated P. heterotremus a relative close relationship with species P. westermani (AF219379.2).